Caracterização e secagem convectiva do bagaço da laranja (Citrus Sinensis L. Osbeck) como biomassa lignocelulósica visando o aproveitamento energético - César, Mariana (2023)
It is estimated that around 50% of the weight of the orange is waste with high potential to be used as bioenergy due to its lignocellulosic characteristics. In this sense, the purpose of the present work was to characterize and dry orange pomace based on the structure present in the citrus residue, formed by epicarp, mesocarp and endocarp. Firstly, the samples were characterized according to immediate and compositional analysis, FTIR and XRD. For drying, a convective dryer was used, where experiments were carried out under operating conditions varying the air speed (1.0 m/s – 1.8 m/s) and air temperature (between 60 ºC and 80 ºC). The biomass presented initial humidity above 72% for the different parts, which consisted of the epicarp, mesocarp and endocarp, however, with variations between the volatile contents (93.26 – 96.61%), ash (2.86 – 72% ) and fixed carbon (between 0.15 and 3.93%). For the compositional analysis, extractive results varied from 5.44 to 17.71% for lignin; 27.41 to 42.45% for holocellulose; 15.31 to 23.83% alpha-cellulose and 8.66 to 18.65% hemicellulose. Thermogravimetric (TG) and derived thermogravimetry (DTG) analyzes were used, which identified three stages of thermal degradation, referring to moisture loss and degradation of hemicellulose, cellulose and lignin. During drying, it was observed that the increase in temperature and air speed influenced mass transport, but internal resistance to diffusion was predominant. The simulation of drying data showed that the Page model was selected as the most appropriate to predict the drying phenomenon with R2 close to unity and with mean square deviations lower than 0.006. The results obtained in this work are of great relevance for predicting the behavior of each lignocellulosic biomass during the convective drying process as well as its physical, chemical and thermal characteristics, being considered promising for energy purposes.